2003
DOI: 10.2337/diabetes.52.4.1014
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Can Alter the Signal Transduction Pathways in the Lens of Rats

Abstract: Diabetes is known to affect cataract formation by means of osmotic stress induced by activated aldose reductase in the sorbitol pathway. In addition, alterations in the bioavailability of numerous extralenticular growth factors has been reported and shown to result in various consequences. We have found that the basic fibroblast growth factor (bFGF) accumulates in the vitreous humor of 3-and 8-week diabetic rats. Consequently, the associating signal transduction cascades were severely disrupted, including upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…This dose has previously been established to prevent ophthalmic effects in diabetic and galactosemic rats. [25][26][27][28][29] Lens changes were also absent in the nondiabetic controls.…”
Section: Resultsmentioning
confidence: 78%
“…This dose has previously been established to prevent ophthalmic effects in diabetic and galactosemic rats. [25][26][27][28][29] Lens changes were also absent in the nondiabetic controls.…”
Section: Resultsmentioning
confidence: 78%
“…Consequently, the associating signal transduction cascades are severely disrupted. These included the up-regulation of the phosphorylation of extracellular signal-regulated kinase (ERK), and of the common stress-associated mitogen-activated protein kinases p38 and SAPK/JNK (Zatechka et al, 2003). It was also reported that a 1:1 mixture of Phellodendron amurense and Aralia elata has the ability to increase glycogen contents in hepatocytes, possibly by stimulating PI3-kinase and ERK2 (Kim et al, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…20,24,49 High blood glucose-induced sorbitol accumulation would generate osmotic stress, which would subsequently activate the ERK1/2 and p38/JNK pathways in the prolonged (∼3 weeks and longer) streptozotocin diabetic rat lenses. 22 Activation of these pathways regulates glucose transporters GLUT1 and GLUT3. 40 Inactive GLUT1 and GLUT3 are stored in cytoplasmic pools.…”
Section: Discussionmentioning
confidence: 99%
“…22 To test if the inhibition of gap junctions by activation of PKC-γ causes disruption of cellular signaling in the lenses of VHG diabetic rats, we determined activation of ERK1/2 and caspase-3, a cell apoptotic stress marker. Activation of ERK1/2 occurs through phosphorylation of Thr202/Tyr204.…”
Section: No Activation Of Erk1/2 or Caspase-3 In The Lenses Of Early mentioning
confidence: 99%
See 1 more Smart Citation